2021
DOI: 10.1002/dev.22149
|View full text |Cite
|
Sign up to set email alerts
|

Fathering behavior, attachment, and engagement in childcare predict testosterone and cortisol

Abstract: The present study examined testosterone (T) and cortisol (Cort) in fathers engaged with caregiving. We collected saliva samples in the mornings and evenings of two consecutive days in 150 fathers of 1‐ to 5‐year‐old children. Fathers completed questionnaires on socioeconomic status, family structure and life, sleep characteristics and body mass index (BMI), and reported on their engagement in childcare. Fathers used smartphone‐based experience sampling throughout 1 week to sample ongoing activities with their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…In contrast, in fathers of 4-to 8-month old infants, higher paternal CORT levels correlated with less proprioceptive touch and neutral affect towards the child, and with less gaze synchrony between father and child (Weisman et al, 2013). Similarly, in fathers of 1-to 5-year-old children, a range of fathering behaviors, including cuddling and joint play, were related to lower CORT (Ahnert et al, 2021). In a previous study in the current sample, we found that higher prenatal CORT, measured during an interaction with an unsoothable crying simulator infant, forecasts lower caregiving quality in fathers six weeks postpartum (Bos et al, 2018).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…In contrast, in fathers of 4-to 8-month old infants, higher paternal CORT levels correlated with less proprioceptive touch and neutral affect towards the child, and with less gaze synchrony between father and child (Weisman et al, 2013). Similarly, in fathers of 1-to 5-year-old children, a range of fathering behaviors, including cuddling and joint play, were related to lower CORT (Ahnert et al, 2021). In a previous study in the current sample, we found that higher prenatal CORT, measured during an interaction with an unsoothable crying simulator infant, forecasts lower caregiving quality in fathers six weeks postpartum (Bos et al, 2018).…”
mentioning
confidence: 77%
“…Indeed, fathers with lower T showed more nurturing behavior towards their 1-year-olds (Kuo et al, 2016), and reported greater involvement in direct (e.g., bathing) and indirect (e.g., washing infant's clothes) childcare (Kuo et al, 2018). Also, fathers' engagement in childcare, attachment to the child, and cuddling appeared more pronounced the greater the T diurnal decline (Ahnert et al, 2021). In contrast, fathers' higher T was associated with increased child abuse risk, less observed positive parenting, and more observed negative parenting towards their 18-month-olds (Rodriguez et al, 2020).…”
mentioning
confidence: 97%
“…Still, our upbringing measure is a limited categorical indicator of sons’ perceptions of their relationships to their fathers and other caregivers. A prospective study designed for these issues would likely use extensive, validated surveys, observational methods, and newer technology-based emotional and behavior sampling techniques geared toward measuring different components of parent–child relational qualities and interactions, including during adolescence ( 77 , 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aligning with prior research linking lower T and greater paternal care (Edelstein et al, 2017;Gettler et al, 2011), they found that fathers' whose T rebounded more steeply were less involved in caregiving, although notably, fathers with more rapidly rebounding T engaged in higher quality care during a challenging parenting task. Ahnert et al (2021) also found that Austrian fathers with greater diurnal declines in T engaged in more nurturant, sensitive caregiving and had stronger father-child attachment; however, fathers whose T declined less across the day participated in more rough and tumble play, which is often emphasized as a pathway by which fathers affect child development. These two studies help highlight the complexity and nuances that are increasingly recognized for individual differences in paternal psychobiology and variable fathering roles.…”
mentioning
confidence: 91%
“…Ahnert et al. (2021) also found that Austrian fathers with greater diurnal declines in T engaged in more nurturant, sensitive caregiving and had stronger father–child attachment; however, fathers whose T declined less across the day participated in more rough and tumble play, which is often emphasized as a pathway by which fathers affect child development. These two studies help highlight the complexity and nuances that are increasingly recognized for individual differences in paternal psychobiology and variable fathering roles.…”
mentioning
confidence: 99%